Trade financing and regional financial institutions from a South-South perspective (UN New YorkUS, 2012)
Reviews the role of regional cooperation in the provision of short-term finance to support trade and suppy chain operations. Considers the medium- and long-term financing needs associated with the process of development. Describes the roles of regional development banks and regional bond markets and the scope for long-term development finance.
Keywords: TRADE